Proteomic analysis of different extracts from barley grains - J. Chmelík; P. Řehulka; M. Střelcová; V. Kubáň; C. Mayrhofer; G. Allmaier (Plant, Soil and Environment, 2002)
Identification of several proteins extracted with various solvents from barley grains was performed by the proteomic strategy based on a combination of gel electrophoresis, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and bioinformatics. The mass spectrometry-based strategy designed for protein identification exhibits good sensitivity and rapid protein identification in comparison to other methods. In order to simplify the protein mixture extracted from grains, we used sequential extractions of grains with various solvents (based on modified Osborne system). Several proteins (e.g. β-amylase, B3-hordein) were identified in this way. It seems that this approach can become an important tool for proteomics of cereals.